Extrapolation of ACOSOG Z0011 trial results—A survey of breast cancer providers. Issue 6 (15th March 2021) - Weiss, Anna; Cooley, Victoria; Al‐Hilli, Zahraa; Ballman, Karla; Poorvu, Nancy; Haffty, Bruce; Hunt, Kelly K.; Nelson, Heidi; Blair, Sarah L.; Boughey, Judy
Abstract: We surveyed breast providers from a national oncology cooperative group to evaluate axillary management recommendations for patients with 1–2 positive sentinel lymph nodes (+SLNs) with scenarios not explicitly included in the Z0011 trial. These scenarios included patients underrepresented (premenopausal, HER2+/triple‐negative tumors, and invasive lobular carcinoma) or excluded (treated with mastectomy or neo‐adjuvant chemotherapy [NAC]) from the ACOSOG Z0011 trial. Survey response rate was 94/149 (64%). For patients in underrepresented groups, 45–63% of providers recommended no further axillary treatment. For mastectomy patients, 45–55% recommended multi‐disciplinary discussion. 83% felt more data are needed to change practice, but 41% believed there would be significant accrual challenges to a clinical trial. For patients treated with NAC, recommendations varied widely. 85% felt more data are needed to change practice, but 26% felt there would be significant accrual challenges. For all scenarios, 86–100% of radiation oncologists recommended axillary radiation, while surgeons more often recommended no further axillary treatment. Traditional randomized trials are likely not feasible to provide answers to these critical management questions, so more pragmatic or big data studies may be needed.